2018
DOI: 10.1051/0004-6361/201732079
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent modification of asteroid family Yarkovsky V-shapes

Abstract: Context. The thermal properties of the surfaces of asteroids determine the magnitude of the drift rate cause by the Yarkovsky force. In the general case of Main Belt asteroids, the Yarkovsky force is indirectly proportional to the thermal inertia, Γ. Aims. Following the proposed relationship between Γ and asteroid diameter D, we find that asteroids' Yarkovsky drift rates might have a more complex size dependence than previous thought, leading to a curved family V-shape boundary in semi-major axis, a, vs. 1/D s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 128 publications
(268 reference statements)
0
9
0
Order By: Relevance
“…However, the role of the 3:1 resonance in transporting 2020 CD 3 into Earth-crossing space from the Main Belt seems unlikely due to its ∼5% source probability. In addition, the Yarkovsky effect is able to transport meter-scale objects like 2020 CD 3 into the proximity of the n 6 resonance, the most likely source of 2020 CD 3 , in <1 Myr if it were to have originated as a fragment at 2.3 au (Bottke et al 2006;Vokrouhlický et al 2015), where most V-type asteroids are found, even if possesses significantly different thermal inertia properties compared to larger, kilometer-scale asteroids (Delbo et al 2007;Bolin et al 2018a). In addition, is apparent from the wide distribution of the 1 km Vesta family fragments covering the entirety of the inner Main Belt (Bolin et al 2017) that the size-dependent velocity distribution of family fragments originating from Vesta could have placed 2020 CD 3 -sized objects anywhere between the nu 6 resonance at ∼2.2 au and the 3:1 resonance at 3.5 au (Carruba & Nesvorný 2016;Bolin et al 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of the 3:1 resonance in transporting 2020 CD 3 into Earth-crossing space from the Main Belt seems unlikely due to its ∼5% source probability. In addition, the Yarkovsky effect is able to transport meter-scale objects like 2020 CD 3 into the proximity of the n 6 resonance, the most likely source of 2020 CD 3 , in <1 Myr if it were to have originated as a fragment at 2.3 au (Bottke et al 2006;Vokrouhlický et al 2015), where most V-type asteroids are found, even if possesses significantly different thermal inertia properties compared to larger, kilometer-scale asteroids (Delbo et al 2007;Bolin et al 2018a). In addition, is apparent from the wide distribution of the 1 km Vesta family fragments covering the entirety of the inner Main Belt (Bolin et al 2017) that the size-dependent velocity distribution of family fragments originating from Vesta could have placed 2020 CD 3 -sized objects anywhere between the nu 6 resonance at ∼2.2 au and the 3:1 resonance at 3.5 au (Carruba & Nesvorný 2016;Bolin et al 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…As anticipated in the previous section, edge effect is mostly a result of having a small number of objects outside the V related to those inside the V (where → 0 would lead to 2 ∕ → ∞). Therefore, edge effect could result as a strong signal in a K vs diagram (commonly used in many previous works as a tool to find family signals; Bolin et al, 2017Bolin et al, , 2018aDelbó et al, 2017Delbó et al, , 2019, even if no family was present. However, we have to point out that: 1) The edge effect is highly dependent on the searching method applied, i.e., whether both-sides or left/right-side are used.…”
Section: Need For Calibrationmentioning
confidence: 99%
“…( ) as function of C; both-and one-(right/left) side scoring in the ( )-ℎ Now we turn our attention to the ( )-ℎ (recall that as and are a function of each other, both or methods are equivalent and based in small changes in the nominal slope). The ℎ was pioneered by Bolin et al (2017Bolin et al ( , 2018a and makes direct use of the characteristic value (Vokrouhlický et al, 2006;Walsh et al, 2013) while the ℎ was applied by Delbó et al (2019). Here we will focus on the ℎ (Bolin et al, 2017(Bolin et al, , 2018a, while a translation for the ℎ should be straightforward.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of the 3:1 resonance in transporting 2020 CD 3 into Earth-crossing space from the Main Belt seems unlikely due to its ∼5% source probability. In addition, the Yarkovsky effect is able to transport meter-scale objects like 2020 CD 3 into the proximity of the ν 6 resonance, the most likely source of 2020 CD 3 , in <1 Myrs if it were to have originated as a fragment at 2.3 au (Bottke et al 2006;Vokrouhlický et al 2015) where most V-type asteroids are found even if possesses significantly different thermal inertia properties compared to larger, km-scale asteroids (Delbo et al 2007;Bolin et al 2018a). In addition, is apparent from the wide distribution of 1 km Vesta family fragments covering the entirety of the inner Main Belt (Bolin et al 2017) that the size-dependent velocity distribution of family fragments originating from Vesta could have placed 2020 CD 3 -sized objects anywhere between the nu 6 resonance at ∼2.2 au and the 3:1 resonance at 3.5 au (Carruba & Nesvorný 2016;Bolin et al 2018b).…”
Section: Orbital Evolutionmentioning
confidence: 99%